Effects of risk perception and agricultural socialized services on farmers' organic fertilizer application behavior: Evidence from Shandong Province, China - Ren, Zhong (Frontiers in Public Health, 2023)
Introduction The application of organic fertilizer is an important measure to control agricultural non-point source pollution, improve the quality of cultivated land and enhance the degree of agricultural green development. Methods Based on the survey data of sample farmers in Shandong Province, China, the binary Probit model is used to analyze the influence of risk perception and agricultural socialized services and their interaction on farmers' organic fertilizer application behavior, and further analyze the difference of influence between groups of risk perception and agricultural socialized services on farmers' organic fertilizer application behavior with different characteristics. Results and discussion We found that risk perception has a significant negative impact on farmers' organic fertilizer application behavior. Farmers with stronger technical risk perception and market risk perception are less likely to apply organic fertilizer. Agricultural socialized services have a significant positive impact on farmers' organic fertilizer application behavior, and can effectively alleviate the inhibitory effect of risk perception on farmers' organic fertilizer application behavior. The roles of risk perception and agricultural socialized services vary greatly among different farmer groups. For older generation, large-scale and pure agricultural farmers, agricultural socialized services can more effectively alleviate the inhibitory effect of risk perception on organic fertilizer application behavior.